THE EFFECT OF PROBIOTIC ADMINISTRATION ON THE GUT–LUNG AXIS IN REDUCING THE INCIDENCE OF PNEUMONIA: A SYSTEMATIC REVIEW - fiohana, puput (IJCNP : INDONESIAN JOURNAL OF CLINICAL NUTRITION PHYSICIAN, 2026)
Introduction: Pneumonia is a major cause of illness and death, especially in critically ill patients. Probiotics have been proposed as a supportive intervention to enhance immune function, maintain gut microbial balance, and strengthen the intestinal barrier against inflammation. Research objectives: The aim of this review is to systematically identify relevant evidence regarding the relationship between probiotics and pneumonia. Methodology: The article employs a systematic review as its methodology. A comprehensive literature search was conducted across PubMed, Google Scholar, and Scopus. The selection of articles for the review was based on established inclusion and exclusion criteria, adhering to the guidelines set forth by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Result: Based on 50 articles, 10 articles were filtered that met the inclusion criteria. The reviewed studies indicated that probiotic supplementation may reduce the severity of pneumonia, particularly ventilator-associated pneumonia (VAP), and improve immune response in critically ill patients. Other research supports that probiotic administration can reduce ICU stays and improve overall good immunity. However, other studies have shown that probiotic administration does not affect the length of stay or therapy in the ICU for pneumonia patients. Conclusion: The administration of probiotics in pneumonia patients provides multiple benefits, particularly by enhancing immunity through the modulation of macrophages within the gut–lung axis. Key words: immune system, pneumonia, probiotik, systematic review